2019
DOI: 10.1117/1.jrs.13.4.044503
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of soil moisture using a vegetation scattering model in wheat fields

Abstract: We develop a vegetation scattering model to eliminate the effect of vegetation and surface roughness on the radar signal. The canopy water content is an important variable associated with the scattering effect of vegetation, and it can be calculated using the leaf area index, which is retrieved from PROSAILH optical model based on Landsat-8 images. The scattering model introduced the direct scattering contribution of underlying ground into the water cloud model. The experimental correlation length was replaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…It was reported that HH polarization could provide a low RMSE value of 0.049 m 3 /m 3 [71] using remote sensing-based vegetation descriptors, in this case Normalized Difference Infrared Index (NDII). Similarly, when canopy water content based on LAI was applied as a vegetation descriptor, an RMSE of 0.039 was recorded [53]. Overall, when RMSE and MAE are carefully evaluated, the cross-polarized HV backscatter coefficient is revealed to be more vulnerable than the co-polarized backscatter HH in terms of polarization response in all Cases 1-5 observed.…”
Section: Vegetation Effects On Soil Moisture Retrieval Based On Polarizationmentioning
confidence: 91%
See 1 more Smart Citation
“…It was reported that HH polarization could provide a low RMSE value of 0.049 m 3 /m 3 [71] using remote sensing-based vegetation descriptors, in this case Normalized Difference Infrared Index (NDII). Similarly, when canopy water content based on LAI was applied as a vegetation descriptor, an RMSE of 0.039 was recorded [53]. Overall, when RMSE and MAE are carefully evaluated, the cross-polarized HV backscatter coefficient is revealed to be more vulnerable than the co-polarized backscatter HH in terms of polarization response in all Cases 1-5 observed.…”
Section: Vegetation Effects On Soil Moisture Retrieval Based On Polarizationmentioning
confidence: 91%
“…The estimation of parameters C pp and D pp are solved using a linear model fitting, following which, the values of C pp and D pp are substituted into Equation (2), which allows for parameter A pp and B pp to be solved using the Nonlinear Least Squares Method (NLSM) [51][52][53][54]. It was noted that using Levenberg-Marquardt (LM) optimization in NLSM, an estimation of A pp and B pp can be made [55].…”
Section: Estimating Parameters Of a B C And D In The Wcmmentioning
confidence: 99%
“…Lately, more and more studies using microwave time series data to estimate the soil moisture of agricultural areas-especially for the crop type winter wheat-have been conducted [19][20][21]. Often, only a single satellite orbit constellation and, therefore, data from one satellite with the same acquisition geometry are used [19,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, more and more studies using microwave time series data to estimate the soil moisture of agricultural areas-especially for the crop type winter wheat-have been conducted [19][20][21]. Often, only a single satellite orbit constellation and, therefore, data from one satellite with the same acquisition geometry are used [19,[22][23][24]. Occasionally, the time series used consists of data from the same satellite but related to different orbits and, thus, various azimuth or/and incidence angles [20,23,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation